The last glacial cycle of the southern Levant: Paleoenvironment and chronology of modern humans. Issue 160 (November 2021) - Frumkin, Amos; Comay, Orr
Abstract: The spectrum of glacial-interglacial environmental shifts in the southern Levant Mediterranean zone is evaluated based upon carbon isotopic records of speleothems from several caves, faunal records of Middle Paleolithic and Upper Paleolithic layers in caves, together with additional evidence from the base levels of the region. The studied evidence suggests that food resources were commonly abundant, but some water scarcity and increase in summer rains occurred during MIS 5e, when soils and C3 vegetation were eliminated, causing soil erosion. This was followed by penetration of summer rainfall and lightning storms from the south, and associated C4 vegetation and fires. Faunal resources remained abundant, and humans using the southern Levant corridor enjoyed also a favorable passage through the greening Sahara Desert during MIS 5e, which was crucial for human and faunal dispersion. Qafzeh and Rantis caves' environmental records indicate xeric grassland-type ecosystem with Afro–Arabian elements that can be attributed to MIS 5e. As the environmental conditions of MIS 5e were unique, faunal and isotopic records within this region can be used in the future as chronologic markers for MIS 5e. During the last glacial period, conditions became gradually cooler and wetter, and C3 vegetation dominated the Mediterranean zone. Lower temperatures promoted the entry of Palearctic mammals. Fluctuations of speleothem δ 13 C increased during the latest Pleistocene – early Holocene, indicating environmental instability through the deglaciation. Significantly, the δ 13 C records indicate that vegetation did not change from the last glacial period to the Holocene in spite of the observed fluctuations. The extreme environmental event of MIS 5e was not repeated during the Holocene in terms of natural vegetation and fauna. Anthropogenic environmental change, accelerating towards the present, is overriding the natural trend.